2017
DOI: 10.1007/s41204-017-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of commercial PbCrO4/TiO2 for photodegradation of rhodamine B in aqueous solution by visible light

Abstract: This study throws light on utilization of visible light in removal dyes from wastewater using commercial PbCrO 4 /TiO 2 (P-25) composite which was prepared by grinding TiO 2 (P-25) with PbCrO 4 to decrease the adhesion properties of PbCrO 4 . As-prepared catalyst was characterized by DRS, XRD and N 2 adsorption-desorption. The morphology was examined by SEM. The photodegradation of rhodamine B (Rh B) product in the presence of PbCrO 4 / TiO 2 (P-25) composite was dependent on the pH of the medium. In 2 \ pH \ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 26 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…As explained before, the photoinduced carriers will originate • OH and O 2 •− radicals from the adsorbed oxygen-rich molecules on the ZnO surface, which will in turn participate in the degradation of RhB in the solution. On the other hand, it has been reported that RhB molecules can be excited by visible light [ 124 , 125 ]. When these molecules are adsorbed on the ZnO surface and are excited by visible light, the excited RhB* can inject electrons into the conduction band of ZnO followed by its conversion into cation radicals RhB •+ .…”
Section: Resultsmentioning
confidence: 99%
“…As explained before, the photoinduced carriers will originate • OH and O 2 •− radicals from the adsorbed oxygen-rich molecules on the ZnO surface, which will in turn participate in the degradation of RhB in the solution. On the other hand, it has been reported that RhB molecules can be excited by visible light [ 124 , 125 ]. When these molecules are adsorbed on the ZnO surface and are excited by visible light, the excited RhB* can inject electrons into the conduction band of ZnO followed by its conversion into cation radicals RhB •+ .…”
Section: Resultsmentioning
confidence: 99%
“…3b), which is lower than that reported in the literature for pure TiO 2 (E g ¼ 3.2 eV). 9,14,16,35 The formation of the TiO 2 /GO/CuFe 2 O 4 nanocomposite causes a narrowing in the TiO 2 bandgap due to the good interactions between TiO 2 and GO in the nanocomposite structure; therefore, GO enhanced the absorption of TiO 2 in the visible light region.…”
Section: Characterization Of Tio 2 /Go/cufe 2 O 4 Nanocompositementioning
confidence: 99%
“…13,14 However, TiO 2 has two major demerits: it possesses a wide bandgap energy value of 3.2 eV for pure anatase, which limits its activity under UV irradiation, and it exhibits rapid electron-hole recombination, which decreases its photocatalytic performance. 15,16 Various strategies, including doping by metallic/nonmetallic species, dye sensitization, as well as coupling with narrow bandgap semiconductors, have been developed to expand its photoresponse into the visible light region, decrease electron-hole pair recombination and increase its activity for the removal of toxic pollutants from industrial effluents. [17][18][19] Besides, an improvement in the photocatalytic activity of TiO 2 has been obtained by loading with carbonaceous materials, especially graphene and graphene oxide (GO), as promising supports for photocatalysts owing to their high carrier mobility and large specic surface area, allowing them consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic needles appear in the microstructure. These needles are lead-chromium oxide (similar to [54] or [37], in which lead-chromium oxide was crocoite in the form of longitudinal crystallites), which gives the surface a greenish-yellowish color.…”
Section: Resultsmentioning
confidence: 99%
“…Although methods for modifying the aluminum surface by anodizing and further processing are known [23,24,27,28,32,33,36,37], such tests have not been performed on recycled alloy 6082. This article shows practical examples of surface treatment of 6082 alloy: solid and its scrap.…”
Section: Introductionmentioning
confidence: 99%